2022
DOI: 10.1111/acel.13600
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer‐like tau accumulation in dentate gyrus mossy cells induces spatial cognitive deficits by disrupting multiple memory‐related signaling and inhibiting local neural circuit

Abstract: Abnormal tau accumulation and spatial memory loss constitute characteristic pathology and symptoms of Alzheimer disease (AD). Yet, the intrinsic connections and the mechanism between them are not fully understood. In the current study, we observed a prominent accumulation of the AD‐like hyperphosphorylated and truncated tau (hTau N368) proteins in hippocampal dentate gyrus (DG) mossy cells of 3xTg‐AD mice. Further investigation demonstrated that the ventral DG (vDG) mossy cell‐specific overexpressing hTau for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…Very little is known about these two types of projections to the dentate gyrus in the context of inter-individual differences in cognitive aging. However, studies have shown that mossy cells [32][33][34] and the SuM 35,36 participate in spatial memory retrieval, and the disruption of their projection to the dentate gyrus may result in the cognitive deficits we observed. Therefore, we have identified for the first time that mossy cells and the SuM are two new potential players in resilience to cognitive aging appearing as early as middle age.…”
Section: Discussionmentioning
confidence: 73%
“…Very little is known about these two types of projections to the dentate gyrus in the context of inter-individual differences in cognitive aging. However, studies have shown that mossy cells [32][33][34] and the SuM 35,36 participate in spatial memory retrieval, and the disruption of their projection to the dentate gyrus may result in the cognitive deficits we observed. Therefore, we have identified for the first time that mossy cells and the SuM are two new potential players in resilience to cognitive aging appearing as early as middle age.…”
Section: Discussionmentioning
confidence: 73%